COFFEE ORDERING SYSTEM - Awang Azlan, Awang Ahmad (Universiti Malaysia Sarawak (UNIMAS), 2023)
The Coffee Ordering System is a web-based application designed to streamline and enhance the process of ordering coffee from a café or coffee shop. This system aims to provide a convenient and efficient way for customers to place their coffee orders, as well as for business owner to manage and fulfill those orders. The system allows customers to access an online platform, which is through the website, where they can browse through the coffee menu, coffee types, customize their orders according to their preferences, and add them to their virtual cart. The system provides a user-friendly interface that facilitates smooth navigation and a seamless ordering experience. Once the order is placed, the Coffee Ordering System sends a notification to the business owner or admin, who can then review and process the order accordingly. This can be done through a dedicated backend interface accessible to the admin, which provides real-time updates on incoming orders. The admin can track the progress of each order, manage inventory, and ensure timely preparation and delivery of the coffee to the customers. By implementing the Coffee Ordering System, cafés and coffee shops can streamline their operations, reduce order errors, and enhance customer satisfaction. It saves time and effort for both customers and business owner, allowing for a more efficient coffee ordering process.